2014
DOI: 10.1155/2014/529305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aggregate Gradation on the Physical Properties of Semiflexible Pavement

Abstract: Semiflexible pavement (SFP), a composite pavement, is formed by filling into a very open porous asphalt skeleton a specifically designed water consistency fluid mortar with a very high early and 28-day strength. The amalgamation of both components will produce a SFP where it will replace the conventional wearing course. The main goal of this investigation is to study the effect of various aggregate gradations towards producing SFP. These include determining the optimum binder, volumetric properties, and durabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 10 publications
0
24
0
3
Order By: Relevance
“…Gradation has an important impact on resilient modulus and strength properties of semi-flexible specimens. Gradation with increased percentage of fine aggregates leads to less porous structure and hence grouts are not capable of full depth penetration, which causes reduction in both strength and abrasion resistance of semi-flexible specimens [22,23].…”
Section: Bitumen Type and Aggregate Gradationmentioning
confidence: 99%
“…Gradation has an important impact on resilient modulus and strength properties of semi-flexible specimens. Gradation with increased percentage of fine aggregates leads to less porous structure and hence grouts are not capable of full depth penetration, which causes reduction in both strength and abrasion resistance of semi-flexible specimens [22,23].…”
Section: Bitumen Type and Aggregate Gradationmentioning
confidence: 99%
“…Similar to asphalt mixtures, gravel particles are either suspended in the mixture or in close contact with each other to form a skeleton structure when high plasticity soil is mixed with gravel. Some scholars have found that, for an asphalt mixture, the particle size and the number of contact points between coarse aggregates have a significant impact on its composition and structure, thus affecting its physical and mechanical properties and pavement performance [29][30][31][32]. ese factors depend to a large extent on the aggregate gradation.…”
Section: Introductionmentioning
confidence: 99%
“…Its high temperature stability is better than that of asphalt pavement, and it has superior deformation resistance, water damage resistance, and skid resistance. Therefore, SFP material is mainly used in long steep slope sections, tunnels, small radius curve roads, toll crossings, urban road intersections, and at bus stops [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%